Winston Churchill the flawed genius of World War II - Catherwood, Christopher (Berkley Caliber, 2009)
Examines the decisions and policies Churchill made in the vital months between June 1940 and December 1941. While Churchill is rightly credited with recognizing the Nazi threat early on, his myriad decisions hindered the Allied cause more than they helped it. From dispatching British troops to North Africa and Greece and establishing the Special Operations Executive, to insisting on the Mediterranean's importance to victory and ignoring George C. Marshall's plan that could have won the war in 1943, Churchill's directives not only extended the conflict, but destabilized several regions that have remained in chaos even at the dawn of the twenty-first century. With profound insight into Churchill's early colonial experiences as well as his first tenure as First Lord of the Admiralty, historian Catherwood offers an honest appraisal of his strategies in a unique perspective that separates the myth from the man.--From publisher description.